Overall trends and individual trajectories of swimming performance in a decade of New Zealand national championships - Hopkins, W. G.; Pike, J. C.; Nottle, C. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: The progression of an athlete`s competitive performance is an important element in the development of talent and selection of events, but little is known about changes in swimmers during their formative years. Here we report effects of calendar year and age on performance of swimmers at an annual national championship and an approach to prediction of future performance of individual swimmers. METHODS: The data were the official performance times of swimmers who had entered at least three New Zealand Age Group and Open Championships in 2000-2009 (65-194 swimmers with 261-769 entries in the 16 stroke and distance combinations for each sex). Each swimmer`s best time in a given event was log-transformed for analysis of changes in performance as percents using a mixed linear model that included a quadratic trend to adjust for gradual overall yearly changes in performance and individual quadratic trends or "trajectories" for the effect of age on each swimmer`s times. Each swimmer`s trajectory was used to estimate age of best performance and to predict performance for several years following the last swim. RESULTS: Most boys` events showed practically linear improvements in mean performance time of 1-3% between 2000 and 2009; girls` breaststroke and butterfly showed similar improvements, but there was little change in most other girls` events. After adjustment for these trends, plots of each swimmer`s times and their individual fitted trend showed that quadratics are appropriate to model age-related changes in performance. Age of best performance was similar for boys and girls but showed greater variation between girls (18.9 ± 1.5 and 18.7 ± 2.8 y respectively, mean ± SD); the range in best age for different strokes and distances was ~2 y. There was adequate precision for most estimates and for prediction of most individuals` performances. A change of coach or location for some swimmers was apparent as a substantial deviation of one or more swims from their quadratic trajectories. DISCUSSION: The overall progression statistics will help coaches and swimmers set realistic goals for race times at the National Championships. Annual implementation of the analysis to update the individual performance trajectories should provide guidance for event selection and talent identification.